Estudantes com Transtorno do Espectro do Autismo (TEA) na escola: desafios para a ação educativa compartilhada - Barbosa, Marily Oliveira (2018)
The entrance of students with Autism Spectrum Disorder (ASD) in the regular school is relatively recent and causes challenges, uncertainties and doubts in educators. The portion of students with ASD who choose the regular school, need and have the right to a quality schooling that promotes the maximum development of their potentialities. Thus, these students need teachers to change their teaching work. To do this, they need teachers to use differentiated methodologies. In view of this, the general objective of this study is developing and evaluating an intervention based on participant research, in order to broaden the shared educational work and to improve access to the curriculum for students with ASD. The specific objectives are: to know the teaching work proposed and performed for the student with ASD in the common classroom and in the Specialized Educational Assistance (SEA); to problematize the process of schooling of the student with ASD with education professionals and with the school support professional; to develop pedagogical dialogues with education professionals and school support professionals in order to promote changes in the schooling process for students with ASD. This study is based on the dialectical historical materialist perspective with a focus on historical cultural psychology and historical-critical pedagogy. Participant research involved the ESA teacher, the classroom teacher, the pedagogical coordinator, the school support professional, the director, and the school vice principal. The instruments used were: documentary research; observation with field diary and video recording; interview; and sessions of pedagogical dialogues with simple autoconfrontation. The data were analyzed in the thematic axes: schooling process for students with ASD; interaction between school professionals and students with ASD; and movement of the school in the development of the participant research. The results pointed that one of the barriers to the schooling of the student with ASD is the action of professionals, mainly regarding the fulfillment of the prescribed ones in their professional functions, when their actions are neglected or delegated to others, there are barriers that hinder the academic development of the student. In addition, it takes joint planning and teacher articulation. When there is individualized educational planning for the TEA student along with the common curriculum and the goals set out by teachers and families, there is possibility of academic development in regular school. It is necessary to carry out new studies on this topic, expanding the sample of teachers and students with ASD, making possible the construction of new knowledge necessary for the modification of the Brazilian educational realities.